2017
DOI: 10.1152/ajpcell.00208.2016
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase-2 mediates zinc deficiency-induced oxidative stress and kidney damage

Abstract: Zn deficiency (ZnD) is comorbid with chronic kidney disease and worsens kidney complications. Oxidative stress is implicated in the detrimental effects of ZnD. However, the sources of oxidative stress continue to be identified. Since NADPH oxidases (Nox) are the primary enzymes that contribute to renal reactive oxygen species generation, this study's objective was to determine the role of these enzymes in ZnD-induced oxidative stress. We hypothesized that ZnD promotes NADPH oxidase upregulation, resulting in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…In vivo. An established protocol (12) was used to induce ZnD in male mice on a C57BL/6 background (8 wk old). Mice (n Ï­ 20) were acclimated to a Zn 2Ï© -adequate (50 ppm Zn 2Ï© , ZnA) diet (diet TD.85420, Harlan Teklad) for 2 wk.…”
Section: Znd Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo. An established protocol (12) was used to induce ZnD in male mice on a C57BL/6 background (8 wk old). Mice (n Ï­ 20) were acclimated to a Zn 2Ï© -adequate (50 ppm Zn 2Ï© , ZnA) diet (diet TD.85420, Harlan Teklad) for 2 wk.…”
Section: Znd Modelsmentioning
confidence: 99%
“…Mouse DCT (mDCT-15) cells (6,19) were grown in DMEM growth medium. The mDCT-15 cells were cultured in 1 nM N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine (TPEN)-or vehicle (DMSO)-containing medium for 24 h to reduce intracellular Zn 2Ï© levels (12). TPEN-exposed mDCT-15 cells were cultured in 1 nM Zn 2Ï© -supplemented medium for 24 h to replete intracellular Zn 2Ï© (12).…”
Section: Znd Modelsmentioning
confidence: 99%
“…ATII-R blockers are considered renoprotective against OS not only by decreasing NOX expression but also by improving eNOS and SOD expression and/or activity [64,103]. Another cause of NOXmediated ROS generation in the kidney appears to be zinc deficiency, as shown by several groups [63] and discussed in more detail below.…”
Section: Nadph Oxidasesmentioning
confidence: 98%
“…Nicotinamide adenine dinucleotide phosphate oxidase (NADPH‐oxidase) is a member of enzymes that are involved in production of ROS. It has been reported that zinc deficiency stimulates up regulation of NADPH‐oxidase . Besides, it has been suggested that zinc inhibits ROS production through prevention of the NADPH‐oxidase activity …”
Section: Possible Mechanistic Model Of Zinc In the Inhibition Of Agesmentioning
confidence: 99%